2016
DOI: 10.1186/s12885-016-2312-3
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine and docetaxel in relapsed and unresectable high-grade osteosarcoma and spindle cell sarcoma of bone

Abstract: BackgroundFew new compounds are available for relapsed osteosarcoma. We retrospectively evaluated the activity of gemcitabine (G) plus docetaxel (D) in patients with relapsed high-grade osteosarcoma and high-grade spindle cell sarcoma of bone (HGS).MethodsPatients receiving G 900 mg/m2 d 1, 8; D 75 mg/m2 d 8, every 21 days were eligible. Primary end-point: progression-free survival (PFS) at 4 months; secondary end-point: overall survival (OS) and response rate.ResultsFifty-one patients were included, with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 27 publications
1
53
0
Order By: Relevance
“…For bone sarcoma, although the number of patients with response evaluable lesions was low in this study (n = 7), RR (14%) and DCR (86%) seemed comparable to those previously reported by other groups (RRs of 9–29% and DCRs of 41–57%) [2124, 26]. Our results and the results reported by other groups, that is, that GD therapy seems to be more effective in bone sarcoma than in soft tissue sarcoma, suggest that GD therapy should be a preferred option, at least in some populations of patients with bone sarcoma.…”
Section: Discussionsupporting
confidence: 89%
“…For bone sarcoma, although the number of patients with response evaluable lesions was low in this study (n = 7), RR (14%) and DCR (86%) seemed comparable to those previously reported by other groups (RRs of 9–29% and DCRs of 41–57%) [2124, 26]. Our results and the results reported by other groups, that is, that GD therapy seems to be more effective in bone sarcoma than in soft tissue sarcoma, suggest that GD therapy should be a preferred option, at least in some populations of patients with bone sarcoma.…”
Section: Discussionsupporting
confidence: 89%
“…A direct comparison of toxicities of adults to children and adolescents is challenging, as most gemcitabine/nab‐paclitaxel clinical trials in adults have used different dosing schemas or included chemotherapy‐naïve patients. In one previous phase I/II trial which included pretreated patients, only patients ≥6 months from last therapy could enroll and only 23% of patients treated at the recommended phase 2 dose (RP2D) received prior chemotherapy . In regard to hematologic toxicity, which makes up the bulk of toxicity found in our patients, the RP2D cohort of this trial found Grade ≥3 neutropenia, anemia, and thrombocytopenia in 73%, 14%, and 28% of patients, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…How do we move forward? The optimal “conventional” chemotherapy regimen remains to be defined, and efforts to identify additional effective cytotoxic combinations, as exemplified by the demonstration of activity for the gemcitabine/docetaxel combination 73 , or to augment the usability of known effective agents by mitigating toxicities, exemplified by adding the cardioprotective agent dexrazoxane to increase doxorubicin exposure 74 , are ongoing. It would be very optimistic to expect anything but limited improvements from such approaches.…”
Section: Future Outlookmentioning
confidence: 99%